Extensive molecular tinkering in the evolution of the membrane attachment mode of the Rheb GTPase - Záhonová, Kristína; Petrželková, Romana; Valach, Matus; Yazaki, Euki; Tikhonenkov, Denis V; Butenko, Anzhelika; Janouškovec, Jan; Hrdá, Štěpánka; Klimeš, Vladimír; Burger, Gertraud; Inagaki, Yuji; Keeling, Patrick J; et al. (Scientific reports, 2018)
Rheb is a conserved and widespread Ras-like GTPase involved in cell growth regulation mediated by the (m)TORC1 kinase complex and implicated in tumourigenesis in humans. Rheb function depends on its association with membranes via prenylated C-terminus, a mechanism shared with many other eukaryotic GTPases. Strikingly, our analysis of a phylogenetically rich sample of Rheb sequences revealed that in multiple lineages this canonical and ancestral membrane attachment mode has been variously altered. The modifications include: (1) accretion to the N-terminus of two different phosphatidylinositol 3-phosphate-binding domains, PX in Cryptista (the fusion being the first proposed synapomorphy of this clade), and FYVE in Euglenozoa and the related undescribed flagellate SRT308; (2) acquisition of lipidic modifications of the N-terminal region, namely myristoylation and/or S-palmitoylation in seven different protist lineages; (3) acquisition of S-palmitoylation in the hypervariable C-terminal region of Rheb in apusomonads, convergently to some other Ras family proteins; (4) replacement of the C-terminal prenylation motif with four transmembrane segments in a novel Rheb paralog in the SAR clade; (5) loss of an evident C-terminal membrane attachment mechanism in Tremellomycetes and some Rheb paralogs of Euglenozoa. Rheb evolution is thus surprisingly dynamic and presents a spectacular example of molecular tinkering.
Keywords: Animals; Euglenozoa; fylogeneze; Phylogeny; zvířata; molekulární evoluce; Cell Membrane; Evolution, Molecular; Humans; protein Rheb; Carcinogenesis; Euglenozoa Infections; Ras Homolog Enriched in Brain Protein; infekce prvoky kmene Euglenozoa; karcinogeneze; buněčná membrána; lidé